Wastewater-based SARS-CoV-2 airport surveillance: key trends at the Cape Town International Airport. (28th February 2023) - Nkambule, Sizwe; Johnson, Rabia; Mathee, Angela; Mahlangeni, Nomfundo; Webster, Candice; Horn, Suranie; Mangwana, Noluxabiso; Dias, Stephanie; Sharma, Jyoti Rajan; Ramharack, Pritika; Louw, Johan; Reddy, Tarylee; et al.
Abstract: Monitoring of SARS-CoV-2 RNA in wastewater has revealed the role of mobility in the transmission of coronavirus disease (COVID-19), and the surveillance of airport wastewater in cities across the world has demonstrated how travel entry points can give an indication of trends in transmission. This study undertook wastewater surveillance at the Cape Town International Airport (CTIA) to assess the use of a WBE approach to provide supplementary information on the presence of COVID-19 at a key air travel entry point in South Africa. Grab wastewater samples ( n = 55) were collected from the CTIA wastewater pump station and analysed using quantitative real-time polymerase chain reaction (qRT-PCR) method. The study found a correlation between the wastewater data and clinical cases reported in the City of Cape Town during various time periods and during the peak of a COVID-19 wave. Highly elevated viral loads in the wastewater were observed at times there was increased mobility through the airport. The study also revealed elevated viral load levels at the airport despite the stricter restrictions and through the lower restrictions. The study findings indicate wastewater surveillance and airports can provide supplementary information to airport authorities to assess the impacts of imposed travel restrictions. HIGHLIGHTS: This is the first published work to report on airport wastewater surveillance in Africa. There was a strong correlation between wastewater data and clinical case data. This study demonstrates the utility of wastewater monitoring at air travel entry points in an African setting. Graphical Abstract